2023
DOI: 10.3390/ma16134758
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Strength Improvements of Ramie Fiber Threads through Combination of Citric Acid and Sodium Hypophosphite Cross-Linking

Asri Peni Wulandari,
Vira Putri Dinda Awis,
Ruly Budiono
et al.

Abstract: Ramie (Boehmeria nivea) is believed to be one of the strongest natural fibers, but it still remains behind synthetic materials in terms of tensile strength. In this study, ramie materials were prepared to evaluate the modification crosslinking effect of natural fiber. The aim is to optimize various concentrations of citric acid (CA) crosslinking by adding Sodium hypophosphite (NaPO2H2), which is activated at different temperatures, to obtain the highest tensile mechanical strength. This crosslinking effect has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…To test the resistance characteristics of the fabric's mechanical properties, tensile strength measurements were conducted as previously described. 59,60 The analysis followed the ASTM D3379 standard using the Shimadzu Universal Testing Machine (UTM) at the Manipal GOK Bioincubator, MAHE, Manipal, Karnataka, India. Fabric specimens were randomly cut to lengths of 50-60 mm for testing.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…To test the resistance characteristics of the fabric's mechanical properties, tensile strength measurements were conducted as previously described. 59,60 The analysis followed the ASTM D3379 standard using the Shimadzu Universal Testing Machine (UTM) at the Manipal GOK Bioincubator, MAHE, Manipal, Karnataka, India. Fabric specimens were randomly cut to lengths of 50-60 mm for testing.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…Dittenber (2012) [ 29 ] reported that ramie fiber, a cellulose-based natural fiber, exhibits the highest mechanical properties among other natural fibers. In our previous research, the modification of ramie fibers through cross-linking methods by adding CA (citric acid) and SHP (Sodium Hypophosphite) was found to enhance the mechanical strength of ramie fibers by up to 20 times [ 30 ]. This highlights the potential of enhancing ramie fibers through refinement methods for various applications.…”
Section: Introductionmentioning
confidence: 99%